A graphene-like metallic cathode host for long-life and high-loading lithium–sulfur batteries. Issue 2 (16th December 2015) - Pang, Quan; Kundu, Dipan; Nazar, Linda F.
Abstract : Nanostructured sulfur host materials that embrace both high electronic conductivity and strong chemisorption towards polysulfides are central to enable high performance Li–S batteries. Abstract : Development of Li–S batteries with long cycle life and high practical capacity is central to enable low-cost, large-scale energy storage. Sulfiphilic cathode materials with strong affinity for lithium (poly)sulfides are a promising new group of candidates to control dissolution/precipitation reactions in the cell, where the improvement of conductivity and the areal sulfur loading is an important objective. Here we report a metallic Co9 S8 material with an interconnected graphene-like nano-architecture that realizes this aim. First-principles calculations coupled with spectroscopic evidence demonstrate the synergistic strong dual-interactions of polysulfides with the host. The three dimensional interconnected structure with hierarchical porosity not only manifests up to a factor of 10 increase of cycling stability (fade < 0.045% per cycle over 1500 cycles at C/2) compared to standard porous carbons but also, more importantly, enables a high-loading sulfur electrode with up to 75 wt% sulfur, and up to 4.5 mg cm −2 areal sulfur loading.